Assessment of the possibility of using a modification of the Colebrook-White formula taking into account the effect of the absolute roughness of the bottom of the stream - Monika Zwolenik; Bogusław Michalec (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The aim of the study was to determine the applicability of the Colebrook-White equation with modifications to its constants K1, K2 and K3, proposed by various authors of the research on water flow resistance in open channels, taking into account the influence of the grain roughness of the mountain stream bottom.